MODELING AND OPTIMIZATION OF GENTIOPICROSIDE ULTRASONIC EXTRACTION FROM GENTIANA ASCLEPIADEA L. UNDERGROUND PARTS - Jovanović, Miloš; Milutinović, Milica; Mudrić, Jelena; Randjelović, Milica; Šavikin, Katarina; Kitić, Dušanka (Archives of Pharmacy, 2023)
Gentiana asclepiadea L. (Gentianaceae) is a medicinal plant traditionally used for the treatment of liver and gastrointestinal disorders. The health benefits of the underground parts of G. asclepiadea are associated with the presence of the major bitter-tasting secoiridoid gentiopicroside. This study aimed to optimize the ultrasonic extraction of gentiopicroside from G. asclepiadea underground parts and develop model with high accuracy and prediction capacity using response surface methodology based on central composite design. The influences of sonication time (5–65 min), ethanol concentration (10–90%), solvent-to-solid ratio (10–50 ml/g), and extraction temperature (20–80 °C) were analyzed as independent variables through 30 experimental runs. Extraction efficiency of gentiopicroside determined by HPLC-DAD was analyzed as the response variable. The second-order polynomial model was determined to be the most suitable for fitting the experimentally obtained responses. The influence analysis reveals significant positive linear effects of sonication time and temperature, a positive interaction effect between extraction time and solvent-to-solid ratio, and negative quadratic effects of solvent-to-solid ratio and ethanol concentration. The calculated optimal extraction conditions were as follows: sonication time of 50 min, ethanol concentration of 52.4%, solvent-to-solid ratio of 35 ml/g, and extraction temperature of 65 °C. The predicted extraction yield under these conditions is 50.75 mg/g dry weight. The method of ultrasonic extraction of gentiopicroside from G. asclepiadea underground parts has been successfully optimized following “green chemistry” principles, and it holds potential applications in the pharmaceutical and food industries.